Evaluation of antioxidant, total phenolsand flavonoids content and antimicrobial activities of Artocarpus altilis (breadfruit) of underutilized tropical fruit extracts - Abdul Wahab, Ridhwan; Jalal, Tara Kamal; Draman, Samsul; Md Isa, Muhammad Lokman; Abdull Rasad, Mohammad Syaiful Bahari; Omar, Muhammad Nor; Ibrahim, Muhammad (2014)
Artocarpusaltilis(breadfruit) pulp, peeland whole fruit were extracted with various solvents such as hexane, dichloromethane (DCM) and methanol the extracts examined for their antioxidant activity usingthe stable 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging test IC50 was ranged from 55±0.89 to4851±0011μg/ml. In the β-carotene bleaching assay the antioxidant activity was 90.02±1.51% for the positive control (Trolox) and 88.34±1.31% for the pulp part of the fruit methanol extract. The total phenolic content of the crude extracts was determined using the Folin-Ciocalteuprocedure, methanol pulp part demonstrated the highest phenol content value of 6570.74±1.14 mg GAE/ g of dry sample. While the total flavonoid content was determined using the aluminium chloride colorimetric assay highest value of 2545.01±0.91 mg QE/ g indicated by pulp part of the fruit methanol extract. Theantimicrobial activity of the crude extracts was tested using disc diffusion method against pathogenic microorganisms: S. aureus, S. epidermidis, B. cereus, S. typhimurium, E. coli, K. pneumonia and C. albican. Methanol extract of pulp part was recorded to have the highest zone of inhibition against Gram-positive and Gram-negative bacteria. The MIC and MBC/MFC for the extracts were also determined using the microdilution method ranged from 4000-63 μg/ml against pathogenic microbes. The MBC/MFC values varied from 250 to 4000 μg/ml. A correlation between antioxidant activity assays, antimicrobial activity and phenolic content was established. The results shows that the various parts of A. altilis fruit extracts promising antioxidant activities have a potential bioactivities due to high content of phenolic compounds.